Congenital Intralabyrinthine Cholesteatoma - Sanjay Prasad; Kiran Prasad; Roya Azadarmaki (Case Reports in Otolaryngology)
A patient with a congenital intralabyrinthine cholesteatoma is presented. High-resolution computerized tomographic scans and intraoperative photomicrographs display features of intralabyrinthine extension. We discuss pathogenetic theories for the development of congenital intralabyrinthine cholesteatoma. The distinction of this condition from congenital cholesteatoma with labyrinthine erosion is discussed.